2018
DOI: 10.3389/fmicb.2018.01064
|View full text |Cite
|
Sign up to set email alerts
|

SbbR/SbbA, an Important ArpA/AfsA-Like System, Regulates Milbemycin Production in Streptomyces bingchenggensis

Abstract: Milbemycins, a group of 16-membered macrolide antibiotics, are used widely as insecticides and anthelmintics. Previously, a limited understanding of the transcriptional regulation of milbemycin biosynthesis has hampered efforts to enhance antibiotic production by engineering of regulatory genes. Here, a novel ArpA/AfsA-type system, SbbR/SbbA (SBI_08928/SBI_08929), has been identified to be involved in regulating milbemycin biosynthesis in the industrial strain S. bingchenggensis BC04. Inactivation of sbbR in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 58 publications
(83 reference statements)
0
26
0
1
Order By: Relevance
“…Furthermore, we found that the promoter region of srbA showed high DNA sequence identity with that of sbbA from S. bingchengensis ( Fig. S1B), whose transcription is directly regulated by SbbR (31). This clearly suggests that the promoter region of srbA (srbAp) might be under the control of SrbR and srbAp is possible a GBL-responsive promoter in S. rapamycinicus.…”
Section: Design Of An Endogenous Qs System-based Crispri Circuit (Eqcmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, we found that the promoter region of srbA showed high DNA sequence identity with that of sbbA from S. bingchengensis ( Fig. S1B), whose transcription is directly regulated by SbbR (31). This clearly suggests that the promoter region of srbA (srbAp) might be under the control of SrbR and srbAp is possible a GBL-responsive promoter in S. rapamycinicus.…”
Section: Design Of An Endogenous Qs System-based Crispri Circuit (Eqcmentioning
confidence: 76%
“…Upon binding to GBL (at a high cell density), the receptor dissociates from target promoters, resulting in transcription derepression. The QS systems have been intensively investigated in several 7 / 39 streptomycetes, such as ArpA/AfsA from Streptomyces griseus (28), ScbR/ScbA from Streptomyces coelicolor (29,30) and SbbR/SbbA from Streptomyces bingchengensis (31). Among them, AfsA, ScbA and SbbA are the GBL synthases responsible for GBL biosynthesis, while ArpA, ScbR and SbbR function as the GBL receptors.…”
Section: Design Of An Endogenous Qs System-based Crispri Circuit (Eqcmentioning
confidence: 99%
“…All the expression plasmids were verified by nucleotide sequencing and then introduced into E. coli BL21 (DE3), respectively. Purification and protein concentrations were performed as described previously (He et al, 2018;Li C. et al, 2019).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…noncyanogenus NMWT1 genomic DNA with primer pairs pscyA1GFPF/R and ScyR1GFPF/R, respectively. The gfp and the strong constitutive promoter SF14 were amplified from pSET152:P sbbA gfp:SF14sbbR with primer pairs GFPF/R and pSF14F/R, respectively (He et al, 2018). First, P A1 and gfp coding region were ligated into pSET152 using the ClonExpress TM MultiS One Step Cloning Kit (Vazyme) to obtain pSET152:P A1 gfp ( Supplementary Table 1).…”
Section: Gfp Reporter Assay In E Colimentioning
confidence: 99%
“…Регуляция образования авермектинов в целом происходит в соответствии с общими закономерностями биосинтеза поликетидов (69) у стрептомицетов (81,82). Факторы регуляции биосинтеза авермектинов делятся на общие и специфические (83)(84)(85)(86)(87).…”
unclassified